FAKTOR FAKTOR PENGHAMBAT REALISASI PELAKSANAAN PEMUNGUTAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (PBB-P2) DIKABUPATEN MANGGARAI(Studi kasus: Peraturan Daerah Kabupaten Manggarai Tentang APBD Tahun Anggaran 2021-2023) - Stanislaus Defretin Parlan; Ferdinandus Ngau Lobo; Benediktus Peter Lay (INTELIGENSIA MEDIA, 2025)
Rural and Urban Land and Building Tax (PBB-P2) is an important component of Local Own-Source Revenue (PAD), which plays a vital role in supporting development and public services at the local level. In Manggarai Regency, the realisation of PBB-P2 revenue often falls short of the targets set in the Manggarai Regency Regional Regulation on the 2021-2023 Fiscal Year Budget, indicating the existence of factors that hinder its collection. This study aims to identify and analyse in depth the inhibiting factors and to determine the efforts made by the Manggarai Regency Regional Revenue Agency in increasing Urban and Rural Land and Building Tax (PBB-P2) revenue. The type of research used is empirical legal research with a sociological juridical approach. The data used in this research is primary and secondary data, with the data collection technique being interviews and the data analysis method used in this research being qualitative descriptive analysis, which explains and describes the data obtained to provide answers to the problems. The results of the study show that the factors hindering the realisation of PBB-P2 tax collection in Manggarai Regency are, first, law enforcement related to the implementation of the 2021-2023 regional budget (APBD) regulations. Legal products are said to be effective if they have been applied and implemented. Second, the factor of taxpayer awareness and compliance. The level of taxpayer awareness of their obligation to pay PBB-P2 is still relatively low, which is exacerbated by a lack of effective socialisation and understanding of the benefits of taxes for regional development. The economic factors of taxpayers, where most of the community has an irregular income, also affect their ability to fulfil their tax obligations in a timely manner. Thirdly, the inaccuracy of tax object data, such as data on ownership and land/building area, as well as slow data updates, often cause discrepancies between field data and recorded data, leading to potential revenue losses. Fourthly, a factor that hinders the implementation of PBB-P2 collection is the lack of supporting facilities or infrastructure. In this case, the infrastructure referred to includes transportation facilities, office facilities, and data management systems. Fifth, the cultural factor of PBB-P2 tax collection is often seen as a burden, not as a contribution to regional development. In the local culture, there is an assumption that land wealth is jointly owned by the community, so they feel they should not have to pay tax on the land. In the process of collecting PBB-P2 taxes, the regional revenue agency conducts socialisation and updates the tax database. The research data shows that the realisation of PBB P2 collection is often not in line with the targets set in the Regional Regulation (Perda) on the Regional Revenue and Expenditure Budget for the 2021-2023 fiscal year. This discrepancy can be caused by various factors. The solution is that the Regional Revenue Agency must update tax object data regularly and accurately, which includes re-data collection, field verification, and data integration with related agencies. For the community, understand the benefits of land and building taxes and know that the PBB-P2 paid will return to the community in the form of development and public services.